Environmental change through capacity building : Africa, the Caribbean and the Pacific - capacity-building related to multilateral environmental agreements (MEAs) in Africa, Caribbean and Pacific (ACP) countries (UNEP NairobiKE, 2017)
Aims to assist 79 countries to enhance their capacities in implementing certain MEAs at the national and regional level.
Keywords: ENVIRONMENTAL LEGISLATION